Use of non-steroidal anti-inflammatory drugs in the treatment of ocular allergy - Janiszewska-Salamon, Julia; Obrok, Monika; Mrukwa-Kominek, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Ocular allergy is a common condition treated by GPs, pediatricians, allergists, and ophthalmologists. The eye is an organ frequently affected by allergic response, as it lacks a mechanical barrier to the entry of allergens. The paper presents the possibilities for using non-steroidal anti-inflammatory drugs in the treatment of allergic conjunctivitis.